Pembentukan Karakter Religius Siswa Kelas IV Pada Mata Pelajaran Akidah Akhlak di Madrasah Ibtidaiyah Swasta al-Mustaqim Tiga Serumpun, Kecamatan Tebas Tahun Pelajaran 2019-2020 - Syaifudin Syaifudin; Weni Weni (TARLIM : JURNAL PENDIDIKAN AGAMA ISLAM, 2021)
The current curriculum is oriented towards character education and is no longer oriented towards achieving competence, especially during the current Covid-19 pandemic, learning cannot be carried out face-to-face but online. This research is intended to dig deeper into the teacher's efforts in shaping the character of students at al-Mustaqim Private Madrasah Ibtidaiya, starting from the findings in the pre-survey that students have been accustomed to good behavior, besides that the teacher always provides exemplary actions and attitudes. Ofcourse this is a unique finding that needs to be investigated more deeply. The research method used is qualitative-descriptive research, which is to collect data in the form of observations and interviews from related parties at MIS al-Mustaqim. Based on the research conducted, it was found that the teacher's efforts in shaping students' religious character were habituation and exemplary, giving motivation and advice. In addition, there are also supporting factors in the form of cooperation between the two parties, parental care, supporting facilities and infrastructure, and synergistic commitment. and the obstacles in the form of lack of student awareness, lack of supervision from the teacher, varied character of students and the technology used is not effective and targeted. Thus, it can be concluded that habituation and exemplary methods are the best efforts that teachers can do to shape student character, even so to form student character is not easy, there must be obstacles to be overcome, so it requires carefulness and patience from the teacher.